Elastic-plastic rotating solid disk with rigid casing - Guven, U; Altay, O (AKADEMIE VERLAG GMBH, 1997)
Subject of the present investigation is an elastic-plastic rotating thin solid disk with constraint to the radial movement in the outer boundary. An exact solution is presented under the Tresca's yield condition its associated flow rule, and linear strain hardening material behaviour.
Keywords: Mathematics; Mechanics